PKM PENDAMPINGAN PENGUATAN USAHA KUBE "SEJAHTERA MANDIRI" DALAM MENGANTISIPASI PANDEMI COVID-19 - Safrizal; Mulia Safrida Sari; Yani Rizal (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
KUBE “Sejahtera Mandiri” which is located in PB. Blang Pasee, Kec. Langsa Kota - Langsa City, is a productive economic group engaged in micro-enterprises to meet the needs of customers around Langsa City. In their daily life, the members have various businesses, such as selling side dishes, candied fruits, mobile phone credit business, making cakes and others, all of which they do to help the family's economy. In October 2010 an idea emerged to create a joint venture as a form of business diversification by utilizing coconut water waste as a raw material to produce nata de coco products. The problems faced are related to the production process, namely the place and production facilities that are considered unhygienic so that it can reduce consumer confidence and relate to the preparation of good KUBE business financial reports. The Community Partnership Program activity team will provide assistance which includes activities to increase knowledge about good and correct Production Processes, as well as business management assistance, especially regarding bookkeeping, so that they can find out the costs, income and benefits of KUBE Sejahtera Mandiri PB. Blang Pasee Langsa City. From the results of the activity, partners gave a positive response, were enthusiastic and were cooperative in participating in all activities. Partners gain insight and skills after participating in this series of training and mentoring activities.